Fundamentals of helicopter dynamics - Venkatesan, C. (Boca Raton : CRC Press, 2015)
'This is an introductory book on helicopter dynamics. The aim of this book is to introduce the students/engineers to the basic principles of helicopter dynamics. The book focuses on three major topics: (i) rotor blade idealization and blade dynamics in flap, lag and torsion modes; (ii) rotor blade aeroelastic stability {coupled flap-lag and coupled flap-torsion}; (iii) coupled rotor-fuselage dynamics. It covers hover, forward flight and other manoeuvre flights. Starting from basic physics of rotating systems, the equations of motion have been derived in vector form.'--
Includes bibliographical references (pages 305-309) and index.
Keywords: Helicopters -- Aerodynamics; Rotors -- Dynamics